Drivers of perceived safety: do they differ in contexts where violence and police saturation feel ‘normal’? - Kochel, Tammy R. (Journal of crime and justice, 2021)
Feelings of safety vary by context, with disordered, high-crime areas typically generating more fear among residents. However, scholars have suggested that when violence permeates the daily routines in an area, it can begin to feel ‘normal.’ Residents may become desensitized to the risky conditions and grow accustomed to a high police presence, more aggressive tactics, and being stopped by police. Thus, lived differences with crime and police may alter the lens through which residents interpret environmental cues about their safety. The current study draws on 820 household surveys of residents from high-, moderate- and low-violence areas in an effort to inform police and communities about strategies that promote feelings of safety within different contexts. Our findings demonstrate that collective efficacy is consistently important to residents’ feelings of safety, across all contexts. Hearing gunfire reduces feelings of safety most in the area with moderate levels of gun violence. The results imply a need to tailor safety strategies to what makes people feel safer in areas with different levels of violence.